Cryptic invasions of Pseudopolydora (Annelida: Spionidae), with description of a new species from Queensland, Australia - Radashevsky, Vasily I.; Malyar, Vasily V.; Pankova, Victoria V. (Zootaxa, 2024)
During surveys worldwide, we collected adult and larval specimens of Pseudopolydora Czerniavsky, 1881 similar to P. achaeta Radashevsky & Hsieh, 2000 and P. rosebelae Radashevsky & Migotto, 2009 far from their type localities in Taiwan and Brazil, respectively. Analysis of sequence data of five gene fragments: mitochondrial COI and 16S rDNA, nuclear 18S rDNA and 28S rDNA, and Histone 3 (3114 bp in total) of individuals from Nha Trang Bay (Vietnam), São Paulo (Brazil), Florida (USA), and the Caribbean Sea (Martinique) confirmed their conspecificity with P. achaeta from Taiwan. Based on the morphology, we also report this species for the first time for the East Sea (South Korea) and provide new records for the north-western part of the Sea of Japan (Russia). The analysis also showed the conspecificity of worms from Vietnam with P. rosebelae from Brazil. Based on the morphology, we also report P. rosebelae for the first time for the Caribbean Sea (Belize), South China Sea (Thailand), and Hawaii. Developed pelagic larvae of P. achaeta and P. rosebelae from Nha Trang Bay are described and illustrated. A worm from the Great Barrier Reef (Queensland, Australia) earlier identified as P. cf. rosebelae, is referred to the new species Pseudopolydora nivea sp. nov. Following our earlier hypothesis about the origin of Pseudopolydora in the Indo-West Pacific Ocean, we explain the occurrence of these worms, including Pseudopolydora floridensis Delgado-Blas, 2008, on the Atlantic coasts of North and South America by unintentional transportation in ballast water, followed by successful invasions. We assume that the penetration of warm waters of the East China Sea through the Korea Strait and the warming of the waters of the Sea of Japan have led to the extension of the range of tropical-subtropical P. achaeta to the north-western part of the Sea of Japan.